On the edge : living with global capitalism / edited by Will Hutton and Anthony Giddens. - Hutton, Will, 1950-; Giddens, Anthony (Vintage, 2001)
This collection of essays charts the contours of contemporary capitalism, analyses the role of the business firm in the new context of innovation and competitiveness, discusses the impact of globalisation, and considers new capitalism.